Facilitadores y obstáculos para la innovación educativa: un estudio exploratorio en cuatro escuelas privadas mexicanas (2014)
The aim of this paper is to present how educational innovation is an essential element in schools. The exercise was conducted in the framework of the course: Innovation and educational processes that is part of the curriculum of the major on Psychopedagogy at UPAEP. We took into account Carbonell (2002) who states in his book: The Adventure of innovation, a number of factors that drive or hinder the educational innovation. From these factors, It is made an inquiry to know for exploratory manner the perception of teachers and leaders of four private schools in the cities of Puebla and Acapulco on elements that promoting and impeding the processes of educational innovation. The results of the study with this small population, although not generalizable show that the elements pointing by Carbonell at point in his work can be useful to analyze the school situation to innovation in different areas and that both factors pointing as facilitators and obstacles are present in the school culture. In general results show a general perception among respondents that there is not a culture of innovation sufficiently consolidated and there is a resistance among teachers to accept and promote innovative strategies in the school.